Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan di PT Dira Finance Bekasi Tambun 2 - Rendy Adi Pratama; Ulta Rastryana; Rini Larasati Irawan (PT. Karya Inovatif Nusantara, 2025)
Human Resource Management (HRM) in an organization aims to manage recruitment, development, and enhance employee work spirit. The purpose of this study is to analyze the influence of work motivation and job satisfaction on employee performance. The research used a quantitative method with a saturated sampling technique involving 50 respondents through the distribution of questionnaires. The results showed that work motivation had a significant influence on employee performance with a t-value of 3.651 > t-table 2.012 and a determination coefficient of 28%. Job satisfaction also had a significant partial effect with a t-value of 2.114 > t-table 2.012 and a contribution of 13.6%. Simultaneously, work motivation and job satisfaction influenced employee performance with an F-value of 16.742 > F-table 3.20 and an R² value of 0.416, indicating that both variables affected employee performance by 41.6%. Therefore, all hypotheses in this study are accepted.